2022
DOI: 10.1371/journal.pone.0267697
|View full text |Cite
|
Sign up to set email alerts
|

The science of YouTube: What factors influence user engagement with online science videos?

Abstract: As the reach of science content in traditional media declines, many institutions and scientists are turning to YouTube as a powerful tool for communicating directly with non-expert publics. They do so with little empirical social science research guiding their efforts. This study explores how video characteristics and social endorsement cues provided by audience members might influence user engagement with online science videos. Shorter videos are more likely to be viewed. Social endorsement cues significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 56 publications
(58 reference statements)
6
18
0
Order By: Relevance
“…No other factor had a significant effect on audience engagement. The number of likes is often seen as a user filter and an indicator of popularity and can reflect video quality 22 35–37. Interestingly, the DISCERN instrument’s category on quality of treatment choices affected the video’s audience engagement in our study.…”
Section: Discussionmentioning
confidence: 65%
“…No other factor had a significant effect on audience engagement. The number of likes is often seen as a user filter and an indicator of popularity and can reflect video quality 22 35–37. Interestingly, the DISCERN instrument’s category on quality of treatment choices affected the video’s audience engagement in our study.…”
Section: Discussionmentioning
confidence: 65%
“…Interestingly, no correlation was found between audience engagement and a video’s DISCERN scores. The number of likes is commonly viewed as a collective filter and as an indicator of popularity, which may reflect video quality [ 19 , 51 , 52 ]. However, our findings suggested that, similar to that in other platforms, the audience on the TikTok platform pay more attention to the identity of the author rather than the content and quality of the video.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have tried to map scientists on Twitter, covering various disciplines (Ke et al, 2017). And while there are several studies that have specifically focused on other social media platforms besides Twitter (e.g., Debove et al, 2021;Hubner & Bond, 2022;Jarreau, Cancellare, et al, 2019;Jarreau, Dahmen, et al, 2019;Yang et al, 2022;Zeng et al, 2021), Facebook seems to remain understudied.…”
Section: Scientists' Social Media Usagementioning
confidence: 99%
“…Since the early days of science communication on social media, new platforms have come to scholarly attention. For example, studies have analyzed science communication on YouTube (Debove et al, 2021;Yang et al, 2022), Instagram (Jarreau, Cancellare, et al, 2019), Reddit (Hubner & Bond, 2022), and even TikTok (Zeng et al, 2021). Moreover, while scientists have adapted well to the changing social media landscape, there has been a lack of engagement on Facebook, even though it is still among the most widely used social media platforms in many countries (Newman et al, 2022) and one of the primary sources from which regular citizens encounter scientific information and issues (Hargittai et al, 2018;Mueller-Herbst et al, 2020).…”
Section: Introductionmentioning
confidence: 99%